Remarks on paraconsistent decision making theory - Abe, J. M.; Silva, J. I. da; Carvalho, F. R. de; Callaos, N.; Lesso, W.; Schewe, K. D.; Atlam, E. (Int Inst Informatics & Systemics, 2003)
In this expository work we show how the para-analyzer can be useful to a variety of applications involving decision making when facing mainly with uncertainty, inconsistent or paracomplete information. The Para-analyzer can be implemented electronically, originating the Para-control, very useful in applications in the area of Robotics and Automation.
Keywords: uncertainty and decision making theory; paraconsistent logics; paraconsistent annotated logics; logic control systems